Theatre’s Flesh, World’s Flesh (Itinera, 2017)
As soon as the light inside the theatre fades (usually very slow, almost stealthily, in order to avoid a brusque transition), a switch of codes of perception takes place. Not from reality to fiction, as if these were two separate worlds, but from one way of watching to another. Watching becomes the key in a strategy between showing and hiding, receiving and hiding back. The spectator is all but passive. All your mental and sensory faculties are focussed on digesting a flood of impressions in the course of a performance. It does not merely involve watching, but it concerns a receptivity that encompasses one’s whole physical being. How can we understand this ‘global’ perception ? What takes really place on a sensory level ? How does a spectator respond to a performance in a theatre landscape were new theatrical forms appeal to varied sorts of stimuli and sensations ? What can we learn from the field of embryology concerning our senses ? And how can we integrate the sensorial dimension into the envelop of the world ? What does it mean to be in the flesh of the theater at the heart of the world ?